Examining Students’ Listening and Speaking Skills in Thai language after Using LINE Assisted Language Practice - Geerativudhipong, Orrathip (FOYER: The Journal of Humanities, Social Sciences, and Education, 2022)
This study was conducted to examine students’ listening and speaking skills performance after learning by LINE activities to improve listening and speaking skills in Thai language out-of-class. The subjects of this study were 108 participants took a Thai language and culture course at the international university in Thailand and participated in this research voluntarily. Two types of instruments were used in this study: experimental and data collection tools. The first was a LINE application and the second was pre-test and post-test of listening and speaking skills in Thai language. Data were analyzed by descriptive statistics and t-test. The result revealed that after learning by LINE activities, mean scores of students’ listening skill (M = 8.52, SD = 1.15, t (48) = 2.15, p = 0.03) and speaking skill (M = 8.20, SD = 0.82, t (48) = 2.09, p = 0.04) in Thai language were significantly.